Work-family psychological contract, job autonomy and organizational commitment - Mohamed Azim, Abdul Mutalib; Ahmad, Aminah; Omar, Zoharah; Silong, Abu Daud (Science Publications, 2012)
Problem statement: With the increase in dual-career couples in the workforce and absence of adequate legal contracts in the form of work-family policies, employees may hold expectations regarding employers obligation based on what has been promised by the organization regarding work-family benefits. Employees expectations of obligations from an employer may depend on psychological mechanisms or psychological contracts rather than formalisms arising from laws. Despite the existence of earlier studies on psychological contract, the contract has been studied as a global concept. Approach: This study had applied the global psychological contract concept to a more specific concept that was work-family psychological contract. Since earlier studies had established the relationship between psychological contract and organizational commitment as well as the effect of job autonomy on this contract, this study examined the mediating role of work-family psychological contract in the relationship between job autonomy and organizational commitment. Using self-administered data were collected from 307 employees in media organizations in Malaysia. Results: Results of correlation analyses revealed that job autonomy was correlated to work-family psychological contract and organizational commitment and work-family psychological contract was related to organizational commitment. The results also indicated that work-family psychological contract partially mediated the relationship between job autonomy and organizational commitment. Conclusion/Recommendations: Employees with greater freedom to make their own decisions at work would have stronger beliefs that the organization can fulfill promises regarding work-family benefits and they can in turn be more committed to the organization.